BCR::ABL1-negative myeloproliferative neoplasms in the era of next-generation sequencing - Mroczkowska-Bękarciak, Aleksandra; Wróbel, Tomasz (Frontiers in Genetics, 2023)
The classical BCR::ABL1-negative myeloproliferative neoplasms such as polycythemia vera (PV), essential thrombocythemia (ET), and myelofibrosis (MF) are clonal diseases with the presence of characteristic “driver mutations” in one of the genes: JAK2, CALR, or MPL. The search for mutations in these three genes is required for the diagnosis of MPNs. Nevertheless, the progress that has been made in the field of molecular genetics has opened a new era in medicine. The search for additional mutations in MPNs is helpful in assessing the risk stratification, disease progression, transformation to acute myeloid leukemia (AML), or choosing the right treatment. In some cases, advanced technologies are needed to find a clonal marker of the disease and establish a diagnosis. This review focuses on how the use of new technologies like next-generation sequencing (NGS) helps in the diagnosis of BCR::ABL1-negative myeloproliferative neoplasms.